Risky banks and macroprudential policy for emerging economies - Victoria Nuguer; José Gabriel García Cuadra (Banco de México, 2016)
We develop a two-country DSGE model with global banks to analyze the role of crossborder banking flows on the transmission of a quality of capital shock in the United States to emerging market economies (EMEs). Banks face a moral hazard problem for borrowing from households. EME's banks might be risky: they can also be constrained to borrow from U.S. banks. A negative quality of capital shock in the United States generates a global financial crisis. EME's macroprudential policy that targets non-core liabilities makes the domestic economy resilient to the volatility of cross-border banking flows and makes EME's households better-off.
Keywords: G28; E44; F42; G21; 330; Global banking; emerging market economies; financial frictions; macroprudential policy